General applicability of fatigue life assessment method for metal laser powder bed fusion parts : variation in material, shape and test conditions - Wits, W.W.; Amsterdam, E. (Elsevier, 2025)
The general applicability of our formerly developed fatigue prediction and life assessment methodology for metal Laser Powder Bed Fusion (LPBF) parts is validated for a new commonly used feedstock material; AlSi7Mg. Moreover, another specimen geometry and surface finish, as well as another fatigue loading condition have been used. The fatigue life assessment method for additively fabricated metal parts uses both the size of LPBF-process inherent initial defects and a material- and process-specific pivot point to accurately predict the fatigue life. An experimental campaign was completed and confirmed that the method is indeed expandable to another material, shape and fatigue loading condition.
Peer review under the responsibility of the scientific committee of the ISEM2025 Conference